2011
DOI: 10.1007/s00127-011-0417-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and migrational impact on the clinical manifestation of depression

Abstract: Depressive symptomatology varies between ethnic groups. These differences are mainly due to ethnicity as such but migration may play an additional role. It is essential for physicians to be aware of atypical presentation forms of depression in minority groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 54 publications
1
19
0
2
Order By: Relevance
“…Many international studies have reported cultural and ethnic variations in reporting depressive symptoms (Deisenhammer et al ., ; Lloyd et al ., ). Thus, there are doubts on the fitness of Western diagnostic system for Asian patients who present differently with clinical depression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many international studies have reported cultural and ethnic variations in reporting depressive symptoms (Deisenhammer et al ., ; Lloyd et al ., ). Thus, there are doubts on the fitness of Western diagnostic system for Asian patients who present differently with clinical depression.…”
Section: Discussionmentioning
confidence: 97%
“…As also shown in Figure 5, centers from highincome countries were reported to have significantly more vegetative symptoms cluster (P < 0.05); upper middle-income countries reported significantly more of the mood (P < 0.001) and cognitive symptoms clusters (P < 0.01); and lower middle-income countries reported less of mood symptoms cluster but more of the cognitive symptoms cluster (P < 0.05). Many international studies have reported cultural and ethnic variations in reporting depressive symptoms (Deisenhammer et al, 2012;Lloyd et al, 2012). Thus, there are doubts on the fitness of Western diagnostic system for Asian patients who present differently with clinical depression.…”
Section: Discussionmentioning
confidence: 99%
“…Dutch was not an exception, as the relevant papers from Dutch scholars were published in English. c) The study sample was formed completely or partially by participants older than 18 (e.g., the parents of children and samples aged [15][16][17][18][19][20][21][22][23][24].…”
Section: Search Strategymentioning
confidence: 99%
“…Eine Vergleichsstudie der depressiven Symptomatik von türkisch-vs. österreichstämmigen Patientinnen zeigte, dass türkische Migrantinnen im Vergleich zu Türkinnen im Herkunftsland und Öster-reicherinnen mehr somatische Beschwerden aufwiesen, was auf die bereits genannten Migrationseffekte zurückzuführen sei. Auch konnten signifikant unterschiedliche Profile der depressiven Symptomatik aufgedeckt werden, wobei beide türkischen Populationen mehr Somatisierungen vorwiesen [41].…”
Section: Introductionunclassified